N6,9-BIS(FERROCENYLMETHYL)ADENINE: SYNTHESIS, CYCLIC VOLTAMMETRIC, SPECTROSCOPIC CHARACTERIZATION, AND DFT CALCULATIONS - ELHAFNAOUI LANEZ; LAZHAR BECHKI; TOUHAMI LANEZ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
n this paper we investigate the synthesis of N6,9-bis(ferrocenylmethyl)adenine starting from the well known quaternary salt (ferrocenylmethy)trimethylammonium iodide and adenine. The obtained compound was characterized by different analytical techniques like: cyclic voltammetry, electronic absorption FT-IR, and 1H NMR spectroscopy. The cyclic voltammogram shows well distinct, stable and reversible redox peaks for the couple ferrocenium-ferrocene in the studied potential range. The lower standard rate constant values of the N6,9-bis(ferrocenyl-methyl)adenine as compared to ferrocene further indicated slower electron transfer kinetics. UV-Vis measurements show three absorption bands attributed to the transitions n→π* and π→π* of aromatic ring and the imine group for N6,9-bis(ferrocenylmethyl)adenine derivative. Finally the energy of border molecular orbitals (EHOMO and ELUMO) of the optimized structure was calculated using DFT/B3LYP method combined with 6-31G basis set in acetonitrile.